Air Traffic Management as a Vital Part of Urban Air Mobility—A Review of DLR’s Research Work from 1995 to 2022 - Bianca I. Schuchardt; Dagi Geister; Thomas Lüken; Franz Knabe; Isabel C. Metz; Niklas Peinecke; Karolin Schweiger (Aerospace, 2023)
Urban air mobility is a rapidly growing field of research. While drones or unmanned aerial vehicles have been operated mainly in the private and military sector in the past, an increasing range of opportunities is opening up for commercial applications. A new multitude of passenger-carrying drone or air taxi concepts promises to fulfill the dream of flying above congested urban areas. While early research has been focusing on vehicle development, solutions for urban air traffic management are lagging behind. This paper collects and reviews the main findings of past urban-air-mobility-related research projects at the German Aerospace Center (DLR) to serve as a basis for ongoing research from an air traffic management perspective.